Pengaruh Penguasaan Mata Kuliah Kewirausahaan dan Dukungan Orang Tua Terhadap Minat Berwirausaha Pada Mahasiswa Pendidikan Ekonomi Semester 6 STKIP PGRI Nganjuk Tahun Akademik 2023/2024 - Siti Nur Dianasyah (Journal of Islamic Economics and Finance, 2025)
In today's era of increasingly fierce competition and globalization, Learning and fostering interest in entrepreneurship has many benefits for Economics Education students. People parents who support and encourage their children to become entrepreneurs can provide the motivation, guidance and resources needed to start a business. provide the motivation, guidance, and resources needed to start and run a business. and run a business. The purpose of this this study to determine the mastery of entrepreneurship courses and parental support on entrepreneurial Parental Support on Entrepreneurial Interest in Economics Education Students Semester 6 STKIP PGRI. Economics 6th Semester STKIP PGRI Nganjuk Academic Year 2023/2024. Ha3 is accepted, then there is a positive influence and significance between the variables of Mastery of Entrepreneurship Subjects And There is an influence of Mastery of Entrepreneurship Courses (X1) and Parent Support (X2) on Entrepreneurial Interest Entrepreneurship Subject Mastery (X1) and Parental Support (X2) on Entrepreneurial Interest (Y) in semester 6 economic education students of STKIP PGRI. Entrepreneurship Interest (Y) in 6th semester economic education students STKIP PGRI Nganjuk Academic Year 2023/2024.